Disability and pain after anterior cervical decompression and fusion : A group-based trajectory analysis - Widbom-Kolhanen, Sara S. (Sage, 2025)
Objectives: This study aimed to identify the clusters of patients with different developmental trajectories of pain and disability after anterior cervical decompression and fusion (ACDF).
Methods: Group-based trajectory analysis among 318 patients undergoing the ACDF.
Results: Three developmental trajectories of disability were identified: "Steadily good functioning," "Improved functioning," and "Steadily poor functioning." Three developmental trajectories of neck pain were identified: "Worsened pain," "Pain relief," and "Steadily severe pain." Two developmental trajectories of arm pain were identified: "Decreased arm pain" and "Severe arm pain with only short-term relief." No associations were found between sex, preoperative pain duration, or body weight and probability to be classified into a particular disability trajectory group. Female sex (relative risk ratio (RRR) 1.78) and longer history of preoperative pain (RRR 2.31-2.68) increased the probability to be classified into a group with steadily severe neck pain. Longer history of preoperative pain increased the probability to be classified into group with severe arm pain with only short-term pain relief (RRR 2.68).
Conclusion: After the ACDF, dissimilar developmental trajectories of pain and disability were identified between the patient clusters. While sex, preoperative pain duration, and body weight were not associated with differences in improvement in disability level, female sex and longer duration of preoperative pain were correlated with more severe neck and arm pain after surgery.